EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIF LEARNINGTIPE STAD DALAM MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN “DAERAH GARONG” KARYA M. SHOIM ANWAR OLEH SISWA KELAS XI SMA NEGERI 1 SIBOLGA TAHUN PEMBELAJARAN 2010/2011 - DAHRIANSYAH SITUMEANG (Asas: Jurnal Sastra, 2012)
This study aims to determine which is most significant and influential efektiifbetween  learning  models  Learning  Cooperatif  STAD  type  of  learning  modelLearning Completed the ability to analyze the intrinsic elements of short stories.The  effectiveness  of  this  model  can  be  seen  from  the  differences  in  learningoutcomes / elements of the intrinsic ability to analyze short stories in Class XIscience  students  SMA  Negeri  1  Sibolga  Learning  Year  2010/2011.  The  studypopulation was all students in grade XI IPA SMA Negeri 1 Sibolga Learning Year2010/2011 which amounted to 170 people. Samples taken in this research clusteras many as 68 people randomly from the population.